Determinants of residential adjustment intentions: insights from low-cost condominium housing in addis ababa, Ethiopia - Alemu, Lissanework Sileshi; Berhanu, Wubshet; Sokkido, Daniel Lirebo (Frontiers in Built Environment, 2025)
Although families often evaluate and modify their housing to meet evolving needs, leading to decline or improvement of neighborhoods, comprehensive studies on residential adjustment intentions remain scarce, particularly in Ethiopia. This study explores determinants of residential adjustment intentions among low-cost condominium residents in Addis Ababa. Using stratified random sampling, 400 households were randomly sampled from inner, intermediate, and outskirt neighborhoods and data were analyzed using descriptive statistics and binomial logistic regression. The study operationalized residential adjustment intentions as dichotomous while residential dimensions satisfaction as ordinal variable with a five-point Likert scale. Results indicate that physical adjustment intentions, like housing modifications and neighborhood improvement participation followed by residential mobility, are the most common, while non-physical adjustment intentions, family size and cognitive adjustments are less frequent. Socio-demographic factors, including age, marriage, family size, number of children, education level, employment type, ownership, and residence duration, influence adjustment intentions, reflecting the impact of life course dynamics. Residential satisfaction is a crucial factor, where satisfaction with neighborhood facilities encourages physical and family size adjustments, satisfaction with public facilities reduces the likelihood of relocation but promote cognitive adjustment, and dissatisfaction with housing characteristics promotes housing unit modifications. These findings underscore the importance of developing housing policies and planning strategies as per the various dimensions of residential satisfaction and adjustment intentions of residents. The study also implies tailored planning interventions to address the unique needs of different groups. Furthermore, the research calls for longitudinal and cross-cultural studies to strengthen its generalizability and practicality of evidence-based interventions.